Digital Detectives: Websleuthing Reduces Eyewitness Identification Accuracy in Police Lineups - Elphick, Camilla; Philpot, Richard; Zhang, Min; Stuart, Avelie; Pike, Graham; Strathie, Ailsa; Havard, Catriona; Walkington, Zoe; Frumkin, Lara A.; Levine, Mark; Price, Blaine A.; Bandara, Arosha K.; et al. (Frontiers in Psychology, 2021)
Eyewitnesses to crimes sometimes search for a culprit on social media before viewing a police lineup, but it is not known whether this affects subsequent lineup identification accuracy. The present online study was conducted to address this. 285 participants viewed a mock crime video, and after a 15-20 minute delay either (i) viewed a mock social media site including the culprit, (ii) viewed a mock social media site including a lookalike, or (iii) completed a filler task. A week later, participants made an identification from a photo lineup display. It was predicted that searching for a culprit on social media containing the lookalike (rather than the culprit) would reduce lineup identification accuracy. There was a significant association between social media exposure and lineup accuracy for the Target Present lineup (30% more of them failed to positively identify the culprit than participants in the other conditions), but for the Target Absent lineup there was no significant association with lineup identification accuracy. The results suggest that if an eyewitness sees a lookalike (where they are expecting to see the culprit) when conducting a self-directed search on social media, they are less likely to subsequently identify the culprit in the formal ID procedure.